Application of Early Childhood Social Care Character Through the Story of the Prophet Muhammad SAW - Titi Wahyu Adibah, Khairiyyah (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2018)
The purpose of applying the character of early childhood social care to bring out the character thatcan imitate his Apostle in socializing, This is an active role in the family environment, communityenvironment, and school environment. Early childhood easily imitates any good or bad behavior.Meanwhile, the application in the character of social care adapts to the environment. In addition tothe supporting environment there are stories of the Prophet Muhammad who reflected the characterof social care. Meanwhile, an educator must be able to provide a variety of learning methods byinserting various interesting and fun stories and stories. This application refers to the Law on socialemotional. Early childhood. The story of the Prophet Muhammad also became an effective mediumto give warnings to students not to fall prey to various kinds of immorality and crime. With a story orstory students will get a touch of values that will affect their character. Especially in the character ofsocial care. An educator can make the story an alternative method for the formation of the soul ofstudents, especially in the affective and psychomotor domains. Educators can place stories or storiesin the learning process